What Do North American Babies Hear? A large‐scale cross‐corpus analysis. Issue 1 (12th October 2018) - Bergelson, Elika; Casillas, Marisa; Soderstrom, Melanie; Seidl, Amanda; Warlaumont, Anne S.; Amatuni, Andrei
Abstract: A range of demographic variables influences how much speech young children hear. However, because studies have used vastly different sampling methods, quantitative comparison of interlocking demographic effects has been nearly impossible, across or within studies. We harnessed a unique collection of existing naturalistic, day‐long recordings from 61 homes across four North American cities to examine language input as a function of age, gender, and maternal education. We analyzed adult speech heard by 3‐ to 20‐month‐olds who wore audio recorders for an entire day. We annotated speaker gender and speech register (child‐directed or adult‐directed) for 10, 861 utterances from female and male adults in these recordings. Examining age, gender, and maternal education collectively in this ecologically valid dataset, we find several key results. First, the speaker gender imbalance in the input is striking: children heard 2–3× more speech from females than males. Second, children in higher‐maternal education homes heard more child‐directed speech than those in lower‐maternal education homes. Finally, our analyses revealed a previously unreported effect: the proportion of child‐directed speech in the input increases with age, due to a decrease in adult‐directed speech with age. This large‐scale analysis is an important step forward in collectively examining demographic variables that influence early development, made possible by pooled, comparable, day‐long recordings of children's language environments. The audio recordings, annotations, and annotation software are readily available for reuse and reanalysis by other researchers. Abstract : We analyzed adult‐ and child‐directed speech (ADS, CDS) in daylong home recordings of infants in 4 N.A. cities. We found large effects of talker (but not child) gender and a small maternal education effect. Intriguingly, older (vs. younger) infants heard relatively more CDS, due to decreasing ADS in the input.